Astronomical Research and Outreach in Georgia - Todua, M.
Interest in astronomy has been significantly increased in Georgia. As a result, the development of astronomical research, education and public outreach are in progress. In Abastumani Astrophysical Observatory - a research institution at Ilia State University - the observational and theoretical studies comprise a wide range of topics in astronomy and adjacent fields: solar system bodies, solar physics, stellar and extragalactic astronomy, theoretical astrophysics, cosmology, atmospheric and near space physics. Georgian scientists are involved in wide international collaboration and participate in a number of networks and projects. Astronomical education at bachelor, master and doctoral levels are held at Ilia University. PhD programs are also offered at other universities. In 2018, under the financial support of the World Bank and Georgian government, the renovation of Abastumani Observatory has been started. International conferences and workshops have been carried out in Georgia. Excursions at the Observatory and public lectures in astronomy throughout the country are carried out. Amateur astronomers organize astronomical events. A private observatory is under construction near Tbilisi. All these puts better perspective for future development of astronomy in Georgia.
Keywords: Astronomy